2021
DOI: 10.1101/2021.12.08.21267378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heart age estimated using explainable advanced electrocardiography

Abstract: Background: Electrocardiographic (ECG) Heart Age conveying cardiovascular risk has been estimated by both Bayesian and artificial intelligence approaches. We hypothesized that explainable measures from the 10-second 12-lead ECG could successfully predict Bayesian ECG Heart Age. Methods: Advanced analysis was performed on ECGs from healthy subjects and patients with cardiovascular risk or proven heart disease. Regression models were used to predict a Bayesian 5-minute ECG Heart Age from the standard resting 10-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…If artifacts are uncorrelated with the outcome of interest, one might choose to leave them unprocessed and thereby potentially even increase the robustness of the learned representation. However, prior studies have shown that peripheral signals and EEG artifacts can be systematically modulated in different patient groups (Golding et al, 2006;Jongkees & Colzato, 2016;Lindow et al, 2023;Wilkinson & Nelson, 2021). This motivated us to systematically study the relationship between different EEG components attributed to CNS versus peripheral generators, which typically differ in terms of spectral and spatial patterns.…”
Section: /54mentioning
confidence: 99%
See 2 more Smart Citations
“…If artifacts are uncorrelated with the outcome of interest, one might choose to leave them unprocessed and thereby potentially even increase the robustness of the learned representation. However, prior studies have shown that peripheral signals and EEG artifacts can be systematically modulated in different patient groups (Golding et al, 2006;Jongkees & Colzato, 2016;Lindow et al, 2023;Wilkinson & Nelson, 2021). This motivated us to systematically study the relationship between different EEG components attributed to CNS versus peripheral generators, which typically differ in terms of spectral and spatial patterns.…”
Section: /54mentioning
confidence: 99%
“…For at least three reasons, we hold that regardless of ICA quality, one has to consider that artifacts are predictive and risk diluting CNS biomarkers: 1) prior knowledge of the change in peripheral and body variables in aging and pathology (Golding et al, 2006;Jongkees & Colzato, 2016;Lage et al, 2020;Lindow et al, 2023;Wilkinson & Nelson, 2021). 2) The sensitivity of machine learning models to pick up even weak and hidden patterns.…”
Section: Artifact Removal Is Essential For Learning Interpretable Bio...mentioning
confidence: 99%
See 1 more Smart Citation